Nosocomial urinary tract aspergilloma in an immunocompetent host: An unusual occurrence - Archana Singal; Chander Grover; Deepika Pandhi; Shukla Das; Bhupinder Kumar Jain (Wolters Kluwer Medknow Publications, 2013)
Fungal infections of the urinary tract are usually encountered following prolonged antibiotic use, instrumentation and indwelling urinary catheters. Candida is the most frequent causative fungus. However, infections with Aspergillus flavus have been reported previously in immune-compromised hosts. We, hereby, report a 32-year-old immunocompetent man diagnosed to have urinary tract infection caused by Aspergillus flavus following instrumentation for the removal of a ureteric stone. The infection was symptomatic, associated with abdominal pain and subsequent passage of fungal masses per urethra. Patient was treated successfully with a prolonged course of broad spectrum antifungal agent itraconazole.